Intraspecific variation of taeniate bisaccate pollen within permian glossopterid sporangia, from the Prince Charles Mountains, Antarctica - Lindström, Sofie; McLoughlin, Stephen; Drinnan, Andrew N (University of Chicago Press, 1997)
Permineralized sporangia from Late Permian sediments of the Amery Group in the Prince Charles Mountains, East Antarctica, are assigned to Arberiella sp. cf A. africana Pant ana Nautiyal. These sporangia contain between 2000 and 3000 taeniate, saccate pollen grains that are predominantly haploxylonoid bisaccate and referable to the palynotaxon Protohaploxypinus limpidus (Balme and Hennelly) Balme and Flayford. However, the sporangia also contain greater than 4% of diploxylonoid bisaccate forms comparable to Striatopodocarpidites cancellatus (Balme and Hennelly) Hart 1963, together with sporadic monosaccate and trisaccate grains that, if found dispersed, would be assigned to several different pollen form genera. Morphometric analysis of in situ bisaccate pollen grains and taeniate bisaccate pollen in the dispersed palynoflora indicates that in situ grains occupy only the smaller end of the total size range. The tendency for in situ grains to cluster into two different size groups may reflect differential predispersal expansion of the corpus. The in situ pollen grains are variable in most qualitative and quantitative features used for taxonomic discrimination of dispersed taeniate bisaccate pollen, and this may lead to unreliable estimates of Late Permian floristic diversity if an overly restrictive species delimitation scheme is used.